(untitled) (Western European Journal of Medicine and Medical Science, 2024)
Parathyroid hormone (PTH) is a small protein that participates in controlling the balance of calcium and phosphate in the body. It has an effect on the skeleton, as it affects the processes of building and breaking down bones. Samples were taken from arthritis and thyroid patients, and the levels of ESR, TSH, T4, T3, PTH, and Ca were measured to determine the level of each of them and to know the relationship between them. The results were TSH (1.650±4.240 p≤0.005)T4 (6.82±44.10 p≤0.005) , T3 (0.727±1.823, p≤0.005) ESR(6.61±47.80 p ≤0.005) ca(0.609±7.311p ≤0.005) The results showed that a high level of ESR indicates the presence of arthritis, a high level of TSH, and a low level of both T 3and T 4indicate hypothyroidism and a low level of PTH, as well as ca. Parathyroid hormone is related to bones, as blood calcium decreases and bone resorption increases. Hypothyroidism also affects the parathyroid gland